Microfluidic centrifugation assisted precipitation based DNA quantification. Issue 9 (1st April 2019) - Banerjee, I.; Aralaguppe, S. G.; Lapins, N.; Zhang, W.; Kazemzadeh, A.; Sönnerborg, A.; Neogi, U.; Russom, A.
Abstract : A microfluidic centrifugation assisted precipitation method for rapid DNA visualization and quantification. Abstract : Nucleic acid amplification methods are increasingly being used to detect trace quantities of DNA in samples for various diagnostic applications. However, quantifying the amount of DNA from such methods often requires time consuming purification, washing or labeling steps. Here, we report a novel microfluidic centrifugation assisted precipitation (μCAP) method for single-step DNA quantification. The method is based on formation of a visible precipitate, which can be quantified, when an intercalating dye (GelRed) is added to the DNA sample and centrifuged for a few seconds. We describe the mechanism leading to the precipitation phenomenon. We utilize centrifugal microfluidics to precisely control the formation of the visible and quantifiable mass. Using a standard CMOS sensor for imaging, we report a detection limit of 45 ng μl −1 . Furthermore, using an integrated lab-on-DVD platform we recently developed, the detection limit is lowered to 10 ng μl −1, which is comparable to those of current commercially available instruments for DNA quantification. As a proof of principle, we demonstrate the quantification of LAMP products for a HIV-1B type genome containing plasmid on the lab-on-DVD platform. The simple DNA quantification system could facilitate advanced point of care molecular diagnostics.